2017
DOI: 10.1016/j.ajhg.2017.06.002
|View full text |Cite
|
Sign up to set email alerts
|

WDR26 Haploinsufficiency Causes a Recognizable Syndrome of Intellectual Disability, Seizures, Abnormal Gait, and Distinctive Facial Features

Abstract: We report 15 individuals with de novo pathogenic variants in WDR26. Eleven of the individuals carry loss-of-function mutations, and four harbor missense substitutions. These 15 individuals comprise ten females and five males, and all have intellectual disability with delayed speech, a history of febrile and/or non-febrile seizures, and a wide-based, spastic, and/or stiff-legged gait. These subjects share a set of common facial features that include a prominent maxilla and upper lip that readily reveal the uppe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
63
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(70 citation statements)
references
References 39 publications
7
63
0
Order By: Relevance
“…Mutations of WDR26 and RAB11B were recently identified for broad NDD phenotypes. 33,34 Most patients with mutations within these two genes show microcephaly. In addition to ASD and microcephaly (−3.92 SD), our patient with the WDR26 LGD DNM also presents ID, seizure, language developmental delay, abnormal MRI, sleeping problems, and ADHD, which are similar to the patients reported here (Table S5).…”
Section: Clinically Relevant Variants Within Known Head-circumferenmentioning
confidence: 99%
“…Mutations of WDR26 and RAB11B were recently identified for broad NDD phenotypes. 33,34 Most patients with mutations within these two genes show microcephaly. In addition to ASD and microcephaly (−3.92 SD), our patient with the WDR26 LGD DNM also presents ID, seizure, language developmental delay, abnormal MRI, sleeping problems, and ADHD, which are similar to the patients reported here (Table S5).…”
Section: Clinically Relevant Variants Within Known Head-circumferenmentioning
confidence: 99%
“…Establishing the unique contributions of FBXO28 or WDR26 individually raises challenges due to 1q41‐q42 breakpoints occurring between these two genes being extremely rare (Figure ). Monogenic pathogenicity reports in either gene have also been absent until a recent 2017 study that demonstrated many 1q41‐q42 MDS features emerge with pathogenic missense/LoF mutations in WDR26 (Skraban et al, ). Although, providing strong evidence of WDR26 's role as a main driver of 1q41‐q42 pathogenesis, not all patients with deletions spanning into the 1q41‐q42 CR include WDR26 .…”
Section: Discussionmentioning
confidence: 99%
“…Most recently in 2017, Skraban et al () described a cohort of patients with de novo mutations in WDR26 resulting in a neurodevelopmental disorder with ID, epilepsy, abnormal gait, and facial dysmorphology. Recognizing WDR26 was included in the deletions of many 1q41‐q42 MDS patients, the group compared the phenotypes of these patients with their own cohort and found consistent clinical overlap leading to the suggestion that WDR26 haploinsufficiency was the primary pathogenic driver in 1q41‐q42 MDS.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Pathogenic variants in various WD domain-containing proteins have been linked to both dominant and recessive human ocular, neurological, skeletal, and genitourinary syndromes. 17,18 All of the variants reported here in WDR37 are upstream of the WD40 domains identified in Uniprot. 13 Similar dominant missense variants upstream of the identified WD domains have been identified in other WD proteins including WDR26 and TBL1XR1.…”
mentioning
confidence: 99%